Standarisasi Resep Kue Sangko Di Nagari Ampang Tareh Lumpo Kecamatan Ampek Jurai Kabupaten Pesisir Selatan - Maharani, Putri; Baidar, Baidar; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2016)
This study aims to find a standard cake recipe sangko, and the quality of the cakes sangko. This research is a qualitative and quantitative research using mixed methods (Mixed Method). This research was conducted in Nagari Ampang Tareh Lumpo from the date of March 7, 2016 until April 7, 2016. The data source is twofold: a source of qualitative data obtained from the expert community, the source of quantitative data obtained from five expert panelists made cakes limited sangko in Nagari Ampang Tareh Lumpo. Based on the quantitative results of organoleptic standardization cake recipe sangko which has been converted followed by organoleptic tests found the quality of the cake sangko include: shape (patterned neat and thickness of Â± 1 cm), color (white enough clean), aroma (coconut and aroma of pandan leaves) , texture (moist and loose), taste (sweet.Kata kunci: standarisasi resep kue sangko, kualitas.